2023
DOI: 10.1186/s12875-023-02119-0
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of a pediatric primary care health-coaching program on change in health-related quality of life in children with mental health problems: results of the PrimA-QuO cohort study

Verena Loidl,
Karina Hamacher,
Martin Lang
et al.

Abstract: Mental health problems (MHP) have a considerable negative impact on health-related quality of life (HRQoL) in children and their families. A low threshold Health Coaching (HC) program has been introduced to bring MH services to primary care and strengthen the role of pediatricians. It comprised training concepts as a hands-on approach for pediatricians, standardization of diagnosis and treatment, and extended consultations. The aim of this study was to evaluate the potential effects of the HC on HRQoL in child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
1
0
1
Order By: Relevance
“…Además, este estudio busca identificar los motivos de consulta que impulsan a estos pacientes y a sus familias a buscar atención en el mencionado departamento. Es imperativo comprender estas motivaciones, ya que es esencial que los servicios de salud mental se diseñen de manera que respondan a las necesidades específicas de esta población (4)(5)(6)(7)(8)(9) .…”
Section: Introductionunclassified
“…Además, este estudio busca identificar los motivos de consulta que impulsan a estos pacientes y a sus familias a buscar atención en el mencionado departamento. Es imperativo comprender estas motivaciones, ya que es esencial que los servicios de salud mental se diseñen de manera que respondan a las necesidades específicas de esta población (4)(5)(6)(7)(8)(9) .…”
Section: Introductionunclassified
“…Following publication of the original article [ 1 ], the author reported that the third affiliation of author Lars Schwettmann was missing. Missing affiliation is added as 8th affiliation in this correction article.…”
mentioning
confidence: 99%